Paranoid Ideation Without Psychosis Is Associated With Depression, Anxiety, and Suicide Attempts in General Population - Na, Eun Jin; Choi, Kwan Woo; Hong, Jin Pyo; Cho, Maeng Je; Fava, Maurizio; Mischoulon, David; Jeon, Hong Jin (The journal of nervous and mental disease, 2019)
This study aimed to characterize the association between paranoid ideation without psychosis (PIP) and suicide attempts in a general population. A total of 12,532 adults were randomly selected as the study sample through one-person-per-household method. Subjects completed a face-to-face interview. Among 12,532 subjects, 471 (3.76%) met criteria for the PIP group. The PIP group was younger with more divorced/widowed/separated and lower income than the non-PIP group. The PIP group showed more than fivefold higher lifetime suicide attempt (LSA) rates and ninefold multiple attempt rates than the non-PIP group. Among PIP symptoms, "spouse was being unfaithful" showed the strongest association with LSA (adjusted odds ratio [AOR], 4.49; 95% confidence interval, 2.95-6.85). Major depressive disorder (MDD) in combination with PIP was associated with a higher risk of LSA (AOR, 15.39; 95% confidence interval, 9.63-24.59) compared with subjects without MDD or PIP. In conclusion, PIP, especially "doubting spouse," was significantly associated with LSA. PIP in combination with comorbid MDD showed higher risk of LSA than subjects without PIP or MDD.